Concept Mapping Strategy in Teaching Learning Economic Concepts and Perception of Students on Teaching Learning Economic Concept Through Concept Mapping - Dorji, Tshewang (Classroom Action Research Journal (CARJO), 2019)
This study aim to investigate the effect of using concept mapping in teaching learning process for teachers and students. The study was carried out in XI Arts at Dechencholing Higher Secondary School under Thimphu Tromde, Bhutan with 35 students. The study was a mixed method. The quantitative data collected through class (pretest and posttest) test were analyzed and interpreted using descriptive statistics such as mean and standard deviation, and inferential statistics such as t-test and level of confidence and statistical significance. The qualitative data collected though observation of group works and presentation, and group reflective journal were analyzed by coding and thematic analysis was drawn to analyze the data. The findings showed concept mapping plays an important role in teaching learning process and has positive opinion towards concept mapping usage. It enhances descriptive ability, understand and help to remember concepts, build confidence and enhance active participation in the classroom. However, all concept cannot be taught through concepts mapping. It is also not always easy to construct all concept map. Teacher should encourage students to continue with concept mapping before students master the technique of concept mapping.KeywordsConcepts, Concept Mapping, Test, Teacher, Teaching Learning